Participation trends according to relative age across youth UK Rugby League - Cobley, S. P.; Till, K. (International Journal of Sports Science & Coaching, 2017)
Relative age effects in sports participation highlight the presence of a significant social and developmental inequality. To assess its prevalence, patterning, and size, this study examined participation trends of youth (ages 7-21 years) Rugby League players registered to local community clubs across the North of England (N = 23,943). Results showed that irrespective of relative age, participation growth occurred from U8 to U12s age categories. However, from U13 to U19s, participation became differentiated with the relatively younger showing earlier and progressively lowering participation proportions (e.g. Q4s - U13-U17 = 24-17%) and were up to 50% less likely to participate (i.e. Q4 vs. Q1 - U15-U16 OR = 0.48 and 0.50). Findings highlight the substantial earlier loss of participation for the relatively younger across youth ages. Player development systems containing inherent selection and differentiation during adolescence are presented as one key process affecting the decision to participate in youth Rugby League. ABSTRACT FROM AUTHOR